Molecular-Based Detection of Enterocytozoon bieneusi in Farmed Masked Palm Civets (Paguma larvata) in Hainan, China: A High-Prevalence, Specificity, and Zoonotic Potential of ITS Genotypes - Zhao, Wei; Ren, Guang-Xu; Qiang, Yu; Li, Jiaqi; Pu, Jinkang; Zhang, Yun; Tan, Feng; Huang, Huicong; Liang, Shaohui; Lu, Gang (Frontiers in Veterinary Science, 2021)
Enterocytozoon bieneusi is a microsporidian and zoonotic species. This study investigated the prevalence and distribution of E. bieneusi genotypes in farmed masked palm civets using nested PCR, as well as assessed their zoonotic potential by phylogenetic analysis of the ITS region of the rRNA region. Here, we collected 251 fecal specimens from farmed masked palm civets (Paguma larvata) from the Hainan Island, China. In total, 128 of 251 samples from the masked palm civets were positive for E. bieneusi, with an average infection rate of 51.0%. Seventeen genotypes were identified in these animals. They included 12 known genotypes -HNR-VI(n = 56), SHR1 (n = 45), SHW7(n = 6), KIN-1 (n = 3), D(n = 3), New1 (n = 3), EbpC (n = 2), CHC5 (n = 1), CHG19(n = 1), CHN4 (n = 1), EbpA (n = 1), Henan-III (n = 1)- and five novel genotypes (HNPL-I to HNPL-II; each one). Phylogenetic analysis categorized these genotypes into two groups. Thirteen of them were members of the zoonotic group 1, and the remaining four genotypes in group 12. In summary, this study has shown that the infection rates of E. bieneusi in masked palm civets from Hainan were relatively high and provides baseline data to control and prevent microsporidiosis in farm-related communities. Therefore, infections in masked palm civets with zoonotic genotypes D, EbpC, CHN4, EbpA, KIN-1, and Henan-III should be considered potential threats to public health.